Upaya Peningkatan Nilai Ekonomi Teh Salak di Kelurahan Karang Joang KM.21 dengan Product Branding dan Digital Marketing - Anggela, Anggela; Prayitno , Budi; Puspita , Anggela; Inayah , Anindya Putri; Definawati, Khairun Amalia; Syafatullah , M. Aqsal Ilham; Muhyiddin , M. Naufal; Jehana , Oktaviani Agnesia; Putri , Yulia Al Zahrah (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
One of the three pillars of higher education (Tri Dharma Perguruan Tinggi) is community service. One way to realize this principle is through participation in the PMMD (Student Community Service Program). This program aims to enable students to apply the knowledge gained at the university to benefit the surrounding community. This particular community service project was motivated by the potential of "Salak Skin Tea," a local product from the KM 21 salak plantation SMEs, which is not yet widely known and lacks optimized marketing efforts. The goal is to enhance the branding and digital marketing of this product by obtaining food safety permits (PIRT), designing attractive packaging, establishing collaborations with e-commerce platforms, creating a sales catalog website, and increasing its economic value. As a result, the project produced a "Salakin Tea" logo and packaging design, secured the PIRT permit, developed the e-catalog website salakintea.com, created promotional social media accounts, and made a documentary video uploaded to YouTube and Instagram. Collectively, these efforts contributed to improved branding, marketing, and the economic value of Salak Skin Tea. This community service initiative by ITK students took place in the Soekarno Hatta KM 21 area.